2013
DOI: 10.1371/journal.pone.0079106
|View full text |Cite
|
Sign up to set email alerts
|

Panobinostat Enhances Cytarabine and Daunorubicin Sensitivities in AML Cells through Suppressing the Expression of BRCA1, CHK1, and Rad51

Abstract: Acute myeloid leukemia (AML) remains a challenging disease to treat and urgently requires new therapies to improve its treatment outcome. In this study, we investigated the molecular mechanisms underlying the cooperative antileukemic activities of panobinostat and cytarabine or daunorubicin (DNR) in AML cell lines and diagnostic blast samples in vitro and in vivo. Panobinostat suppressed expression of BRCA1, CHK1, and RAD51 in AML cells in a dose-dependent manner. Further, panobinostat significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 52 publications
(51 reference statements)
12
86
0
Order By: Relevance
“…5A and B). Consistent with our previous studies, 38 CHK1 levels were decreased following panobinostat treatment and were accompanied by decreased levels of p-CDC25C. Surprisingly, MK-1775 treatment alone also caused significant decrease of CHK1, though it had no effect on CDC25C phosphorylation ( Fig.…”
Section: Panobinostat Synergistically Enhances Mk-1775-induced Cell Dsupporting
confidence: 92%
See 1 more Smart Citation
“…5A and B). Consistent with our previous studies, 38 CHK1 levels were decreased following panobinostat treatment and were accompanied by decreased levels of p-CDC25C. Surprisingly, MK-1775 treatment alone also caused significant decrease of CHK1, though it had no effect on CDC25C phosphorylation ( Fig.…”
Section: Panobinostat Synergistically Enhances Mk-1775-induced Cell Dsupporting
confidence: 92%
“…38,53,56 The present findings provide support for the clinical development of panobinostat in combination with MK-1775 for the treatment of AML.…”
Section: Discussionsupporting
confidence: 68%
“…37,38,47,48 Recent evidence has also highlighted the role of NF-kB, DNA damage, cell cycle checkpoint, and DNA repair in HDACI lethality. [49][50][51][52] It therefore seemed plausible that complementary HDACI and MLN4924 MOAs might result in enhanced antileukemia activity. Indeed, the present results indicate that these agents interact synergistically against AML cell lines, primary AML/MDS cells, and LIC-enriched primitive cells, including those carrying diverse genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many clinical trials investigating the role of HDACIs in combination therapies (NCT01242774, NCT01742793, NCT02061449, and NCT02145715, clinicaltrials.gov). Previous work from this lab has demonstrated the ability of HDACIs to synergize with standard chemotherapeutic agents, at least in part by enhancing DNA damage [2831]. Importantly, we recently demonstrated that treatment with the pan-HDACI panobinostat (LBH589) was able to down-regulate CHK1 [28,29].…”
Section: Introductionmentioning
confidence: 99%